A simplified model to estimate buckling temperatures in oil storage steel tanks. (28th December 2021) - Godoy, Luis A.; Pantousa, Dafni
This paper presents the analytical formulation and numerical results for a two degree-of-freedom model representing the thermal buckling behaviour of vertical storage tanks. The model is an extensible column with a simple support at the base, an elastic spring at the top, and an elastic lateral foundation, subjected to a uniform temperature field. The critical temperature is derived from an energy formulation using geometric nonlinearity and elastic material behaviour. Validation of the model was done by comparison with finite element results of tanks available in the literature. It is shown that good estimates of critical temperatures are obtained from the present model, with maximum differences in the order of less than 10%. The model may also be used in fragility studies of tanks under an adjacent fire. An illustration of the evaluation of fragility curves is shown, indicating estimates of damage due to thermal buckling and at a failure state.